Meetings About Migratory Experiences: Nepalese Immigration in Rural and Urban Settings - Pereira, A.; Rahman, S. (Meetings About Migratory Experiences: Nepalese Immigration in Rural and Urban Settings, 2018)
Synthetic presentation combining some of the main findings in her PhD thesis (Nepalese businesses in Lisbon) with some of the main findings resulting from the Audax-CIES project about the Nepalese in agriculture in Portugal, and discussing the relevance of transnational networks in both settings.